Development and Assessment of Exceptional Quality Biosolids Products for Urban Gardens. Issue 4 (2nd October 2018) - Alvarez-Campos, Odiney; Evanylo, Gregory K.; Badzmierowski, Mike J.
Abstract: Exceptional Quality (EQ) biosolids may be developed into products that can rehabilitate disturbed urban soils for the production of garden vegetables. The objectives of this study were to compare newly developed EQ biosolids products specially tailored for urban soil use with those of established products for the purpose of identifying their capability to support germination and plant growth, as well as to quantify their plant available nitrogen (N) and phosphorus (P). Seven EQ biosolids products and an inorganic fertilizer control were compared in greenhouse bioassays employing soybean ( Glycine max L.) and tall fescue ( Festuca arundinacea Schreb.) to assess product quality and nutrient availability. The EQ biosolids were derived from treatment processes such as thermal drying, composting, and blending with complementary organic and mineral materials. The EQ biosolids products applied at an estimated equivalent agronomic N rate enabled adequate germination and plant growth. The N uptake by tall fescue grown with the biosolids amendments compared with known rates of inorganic N confirmed organic N availability to be approximately 40%, 20%, and 15% for thermally dried, blended, and composted EQ biosolids products, respectively. The application of these products at agronomic N rates to a soil testing adequate in P increased soil P saturation to 20%–35%, a normal range for soil not excessively enriched with P. The availability of N and P in the EQ biosolids products will permit their agronomically beneficial and environmentally sound use in urban soils.